Calculation of theoretical transmission loss in trunk gas pipeline. (December 2019) - Xie, Ying; Wang, Xingzhi; Mai, Fangrui
Owing to the limited accuracy and measurement uncertainty of the instruments installed in gas pipeline systems, it is impossible to completely avoid transmission loss during transportation of natural gas. This study established an uncertainty model for the measurement system determining the complex flow rates of trunk gas pipelines, analyzed the uncertainty calculation methods of different metering systems, and developed a calculation method for determining the theoretical transmission loss. Application showed that the theoretical transmission loss serves not only as an early warning regarding a transmission loss, but also as a guide to the pipeline enterprise for determining the transmission loss assessment index. If the actual transmission loss rate is smaller than the theoretical transmission loss rate during the calculation cycle, it means that the pipeline metering system is working normally. Otherwise, it is necessary to immediately investigate the reason behind the transmission loss and implement corresponding measures.